Place attachment, activation of personal norms, and the role of emotions to save water in scarcity - Peyman Arjomandi A.; Masoud Yazdanpanah; Tahereh Zobeidi; Nadejda Komendantova; Akbar Shirzad (Environmental and Sustainability Indicators)
Water bodies across (semi)arid regions are being pressured by climate change and agriculture. Aptly, in Iran, Urmia Lake's fate is in contestation of these two stressors. Whereas climate change mitigation mandates a huge far-lasting global endeavor, some regional adaptations may support the lake to survive ecologically. This needs accountable actions by both institutions and individuals, contributing to the agricultural dynamism. To ensure the effectiveness of institutional lake restoration plans, the consent, cooperation, and active participation of farmers are essential. The critical issue is to know how to persuade farmers and foster prudent water consumption as the prime strategy. This requires understanding farmers intention and behavior in relation to water conservation. To explore this in the region, a specific sociopsychological model was developed. Utilizing the Norm Activation Model enriched by the constructs of Place Attachment and Expression of Emotion, farmers' moral water conservation behavior in the Urmia Lake Basin was investigated. The results of structural equation modeling revealed that all factors of the model influence the water conservation intention and behavior. While awareness of consequences strongly affects personal norms and appraisal of responsibility, place attachment and appraisal of responsibility positively impact emotions and correspondingly emotions and place attachment affect intention significantly. Whereas personal norms were influenced by awareness of consequences and appraisal of responsibility, they impact behavior and intention significantly and eventually intention makes the strongest relationship with behavior. Uncovering this, the study aims to expose further pragmatic insights for credible and sustainable environmental management policies.